Pengaruh Lingkungan dan Kepuasan Kerja terhadap Kinerja Karyawan di PT. Rizky Putra Raja Karawang - Apriliani, Tiara; Rismayadi, Budi; Pertiwi, Wike (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research aims to find out about several influences related to the influence of the environment and job satisfaction on the performance of PT employees. Rizky, son of the King of Karawang. The method used in this research is quantitative. This research was conducted at PT. Rizky, son of the King of Karawang. The sample collection technique uses all employees of PT. Rizky Putra Raja Karawang, totaling 105 employees. To determine the number of samples used, use the Slovin formula with a margin of error of 10% and the results are 52 employees who were used as respondents. The analysis model used in this research is multiple linear regression analysis using the f-test and t-test with a level of 5%. The research results show that there is a partial influence between the influence of the environment on employee performance and the t table value (6.120> 1.676 or t count > t table). Meanwhile, there is a partial influence of job satisfaction on employee performance with the t table (2.833 > 1.676.